Civil Engineering Colloquium 2020 / Dr Kuan Woei Keong - Kuan, Woei Keong (Unit Penerbitan FKAPP, 2020)
Publication and Staff Training Units of Faculty of Civil Engineering had successfully organised the 4* Civil Engineering Colloquium on the 4th Mar 2020 in Universiti Teknologi MARA, Cawangan Pulau Pinang. The colloquium was opened to our academic staff and post-graduate students to present their research studies. During the colloquium, 35 participants had presented their research outcomes in a wide variety of discipline in civil and environmental engineering. Dr. Masyitah Md Nujid, Mdm. Shahreena Melati Rhasbudin Shah and Ts. Syahrul Fithry Senin were awarded as the best presenters in this event. This event has successfully provided a platform for om academic staff to share their research ideas and promote their research findings. The articles submitted by the participants were also compiled and published in the Proceedings of Civil Engineering Colloquium 2020 in October 2020.